Pelaksanaan Penerimaan Peserta Didik Baru Sistem Zonasi - Saipul Annur; Sumarto Sumarto; Adhelmi Adhelmi; Amil Salim (Departement of Mathematics Education, 2024)
This research examines the implementation of the zoning system policy in Admission of New Students (PPDB) at SMA Negeri 4 Musi Banyuasin. The zoning system, which is regulated by Minister of Education and Culture Regulation Number 17 of 2017, aims to ensure equal access to education by prioritizing student admission based on distance from school. This study uses a qualitative descriptive approach to describe the phenomenon of implementing the zoning system at SMA Negeri 4 Musi Banyuasin, and evaluate its impact on access to education, quality of learning, and community perception. The research results show that the implementation of the zoning system has had a positive impact in increasing access to education for students who live around the school. This system makes it easier for parents to control their children and encourages students with intermediate academic abilities to improve their performance. However, the zoning system also raises several challenges. High achieving but out-of-zone students are often unable to access their favorite schools, and some students feel pressured by the higher academic demands at top schools. This study also found that the implementation of this policy was not fully understood by the public, resulting in confusion and dissatisfaction. Therefore, more effective communication and more equitable provision of resources is needed to ensure the success of zoning policies. By improving these aspects, the zoning system can be more optimal in achieving the goal of equal distribution and improving the quality of education throughout the region.